Functionally Active Antibodies to the Angiotensin II Type 1-Receptor Measured by a Luminometric Bioassay Do Not Correlate With Clinical Manifestations in Systemic Sclerosis: A Comparison With Antibodies to Vascular Receptors and Topoisomerase I Detected by ELISA - Bankamp, Lukas; Preuß, Beate; Pecher, Ann-Christin; Beucke, Nicola; Henes, Jörg; Klein, Reinhild (Frontiers in Immunology, 2021)
Objectives 1) To detect functionally active antibodies(abs) to the angiotensin II type-1-receptor (AT1R) by a novel luminometric assay. 2) To assess their prevalence in systemic sclerosis (SSc), other collagen disorders, as well as in further chronic inflammatory disorders including autoimmune, toxic and chronic viral diseases. 3) To compare these abs with anti-AT1R antibodies by ELISA as well as with antibodies to endothelin-type-A receptors (ETA1) and to topoisomerase I (topo-I) with respect to their specificity and clinical relevance. Methods Sera from 98 SSc-patients, 110 patients with other chronic inflammatory rheumatic disorders, 97 patients with autoimmune liver diseases, 57 patients with toxic or chronic viral liver diseases and 36 healthy controls were analyzed. A luminometric bioassay was established with Huh-7-cells constitutively expressing the AT1R. Patients’ sera were also tested by commercially available ELISA for anti-AT1R, -ETA1- and by an in-house ELISA for anti–topo-I-abs. Results Fifty-two percent of the SSc-patients had functionally active anti-AT1R-abs with stimulatory (34%) or inhibitory capacity (18%). They were present also in up to 59% of patients with other rheumatic diseases but only 22% of healthy individuals (sensitivity 52%, specificity 53%). The functionally active antibodies detected by the luminometric assay did not correlate with anti-AT1R-, -ETA1- or -topo-I-abs measured by ELISA, but there was a strong correlation between anti-topo-I-, AT1R-, and -ETA1-ab reactivity measured by ELISA. Sensitivities of 55%, 28% and 47% and specificities of 66%, 87%, and 99% were calculated for these anti-AT1R-, -ETA1-, and anti-topo-I-abs, respectively. Functionally active abs did not correlate with disease severity or any organ manifestation. In contrast, abs to topo-I, AT1R, and ETA1 were associated with digital ulcers, pulmonary- and esophageal manifestation. Conclusions Functionally active anti-AT1R-abs can be detected in SSc-patients but do not correlate with disease activity. They are not specific for this disease and occur also in other autoimmune disorders and even viral or toxic diseases. Also, the vascular antibodies detected by ELISA are not SSc-specific but correlated with disease manifestations. In contrast, anti-topo-I-abs were confirmed to be a highly specific biomarker for both, diagnosis and organ manifestations of SSc.